Evaluasi Kebijakan Pendaftaran Tanah dalam Program Kota Lengkap di Kota Pontianak - Fadilla, Daffa; Nurhidayati, Ely; Wulandari, Agustiah (REKSABUMI, 2025)
The Complete City Program, part of the Systematic Complete Land Registration (PTSL) policy, aims to enhance legal certainty of land through systematic registration and improvement of land data quality. Implemented in Pontianak City since 2020, the program achieved the status of Complete City in 2024. However, challenges such as residents’ absence and refusal during field verification have hindered its implementation. This study evaluates land registration policy in supporting the Complete City Program in Pontianak Kota District. Data collection was conducted through both primary and secondary sources, analyzed using a mixed-method research approach. Primary data were obtained through interviews with officials from the Pontianak City Land Office (BPN), the Pontianak City Revenue Agency (Bapenda), and local village administrations involved in the program. Meanwhile, secondary data were derived from official documents, legal regulations, and relevant literature. The findings show that Pontianak Kota District achieved a high success rate of 96%, although it did not yet meet the standard criteria of success. Sungai Bangkong Subdistrict met the success criteria with 97.60%, while Darat Sekip (93.72%), Mariana (93.12%), Tengah (92%), and Sungai Jawi (94.72%) remained below the success criteria. The Complete City Program in Pontianak Kota District has been efficient, responsive, well-targeted, and equitable. Its benefits are evident in the improvement of land administration services. However, its effectiveness is still constrained by low community participation as well as insufficient resources and budget, which hinder the achievement of targets. Strengthening public outreach and inter-agency coordination is necessary to achieve comprehensive and optimal outcomes.